Gamifying Virtual Exploration of the Past 350 Million Years of Vertebrate Evolution - Mead, Chris; Bruce, Geoffrey; Taylor, Wendy; Buxner, Sanlyn; Anbar, Ariel D. (Frontiers in Education, 2022)
Surviving Extinction is an interactive, adaptive, digital learning experience through which students learn about the history of vertebrate evolution over the last 350 million years. This experience is self-contained, providing students with immediate feedback. It is designed to be used in a wide range of educational settings from junior high school (~12 years old) to university level. Surviving Extinction’s design draws on effective aspects of existing virtual field trip-based learning experiences. Most important among these is the capacity for students to learn through self-directed virtual explorations of simulated historical ecosystems and significant modern-day geologic field sites. Surviving Extinction also makes significant innovations beyond what has previously been done in this area, including extensive use of gamified elements such as collectibles and hidden locations. Additionally, it blends scientifically accurate animations with captured media via a user interface that presents an attractive, engaging, and immersive experience. Surviving Extinction has been field-tested with students at the undergraduate, high school, and pre-high school levels to assess how well it achieves the intended learning outcomes. In all settings we found significant gains pre- to post-activity on a knowledge survey with medium to large effect sizes. This evidence of learning is further supported with data from the gamified elements such as the number of locations discovered and total points earned. Surviving Extinction is freely available for use and detailed resources for educators are provided. It is appropriate for a range of undergraduate courses that cover the history of life on Earth, including ones from a biology, ecology, or geology perspective and courses for either majors or non-majors. Additionally, at the high school level, Surviving Extinction is directly appropriate to teaching adaptation, one of the disciplinary core ideas in the next generation science standards. Beyond providing this resource to the educational community, we hope that the design ideas demonstrated in Surviving Extinction will influence future development of interactive digital learning experiences.